2021
DOI: 10.1038/s41467-021-26573-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental quantum simulation of superradiant phase transition beyond no-go theorem via antisqueezing

Abstract: The superradiant phase transition in thermal equilibrium is a fundamental concept bridging statistical physics and electrodynamics, which has never been observed in real physical systems since the first proposal in the 1970s. The existence of this phase transition in cavity quantum electrodynamics systems is still subject of ongoing debates due to the no-go theorem induced by the so-called A2 term. Moreover, experimental conditions to study this phase transition are hard to achieve with current accessible tech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…[25] that the quantum Rabi model (a single twolevel emitter coupled to a single mode bosonic field) also can undergo a SPT, when the ratio of atomic transition frequency Ω to the field frequency ω approaches infinity, i.e., Ω/ω → ∞. Such SPT requires a large light-matter interaction strength located in the ultra-strong coupling regime [26][27][28][29][30][31][32][33][34], which has been probed in a single trapped ion setup [35,36] and nuclear magnetic resonance (NMR) quantum simulator [37] with the great progress of experimental technologies. Motivated by the SPT of the Rabi model, there has been considerable amount of stud- * xinyoulu@hust.edu.cn ies concentrating on the extended Rabi models [38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…[25] that the quantum Rabi model (a single twolevel emitter coupled to a single mode bosonic field) also can undergo a SPT, when the ratio of atomic transition frequency Ω to the field frequency ω approaches infinity, i.e., Ω/ω → ∞. Such SPT requires a large light-matter interaction strength located in the ultra-strong coupling regime [26][27][28][29][30][31][32][33][34], which has been probed in a single trapped ion setup [35,36] and nuclear magnetic resonance (NMR) quantum simulator [37] with the great progress of experimental technologies. Motivated by the SPT of the Rabi model, there has been considerable amount of stud- * xinyoulu@hust.edu.cn ies concentrating on the extended Rabi models [38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts have been devoted to exploring many-body quantum phases emerging in light-matter coupling systems using different platforms such as cavity and circuit QED [1][2][3][4], and cold atoms in optical lattices [5][6][7]. The rapid development of such platforms offers high control and tunability, allowing for the exploration of richer phase diagrams with more complex critical behaviors, for example, the study of tricritical points (TCPs) and higher-order critical points (multicritical points).…”
Section: Introductionmentioning
confidence: 99%
“…Other effort to circumvent the difficulty of reaching a consensus on the existence of the AT is to find possibility to cancel the AT [76][77][78]. It has been suggested that the disappearing SPT of the Rabi (Dicke) model in the presence of the AT can be regained by combining the optomechanics and CQED [77,78].…”
mentioning
confidence: 99%